Eye-Tracking in Immersive Virtual Reality for Education: A Review of the Current Progress and Applications - Mikhailenko, Maria; Maksimenko, Nadezhda; Kurushkin, Mikhail (Frontiers in Education, 2022)
The concept of using eye-tracking in virtual reality for education has been researched in various fields over the past years. With this review, we aim to discuss the recent advancements and applications in this area, explain the technological aspects, highlight the advantages of this approach and inspire interest in the field. Eye-tracking has already been used in science for many decades and now has been substantially reinforced by the addition of virtual and augmented reality technologies. The first part of the review is a general overview of eye-tracking concepts, technical parts, and its applications. In the second part, the focus shifted towards the application of eye-tracking in virtual reality. The third part, first the description of the recently emerged concept of eye-tracking in virtual reality is given, followed by the current applications to education and studying, which has not been thoroughly described before. We describe the main findings, technological aspects, and advantages of this approach.